ASUHAN KEBIDANAN PADA NY “E’’ MASA HAMIL, BERSALIN, NIFAS, NEONATUS, DAN KELUARGA BERENCANA DI UPT PUSKESMAS BANGSAL MOJOKERTO - Dyah Siwi Hety, M.Kes; Leni Syarifatul Husna (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
The Maternal Mortality Rate in Indonesia is still high. The existence of comprehensive monitoring through Continuity of care (COC). Comprehensive services, which were complete services, starting from the period of pregnancy, parturition, post partum, neonatal and family planning, were carried out with midwifery management and SOAP documentation. Midwifery care was given to Mrs